Time-motion analysis of Italian elite women's basketball games: Individual and team analyses - Conte, D.; Favero, T. G.; Lupo, C.; Francioni, F. M.; Capranica, L.; Tessitore, A. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to assess elite women's basketball game performance. Five elite women's games (3 Italian first division and 2 Euroleague) were analyzed for individual and team time-motion analyses. The individual analysis evaluated the players' movement patterns with particular focus on high-intensity activity (HIA), sprint activity, and repeated sprint events (RSEs). Team analysis included live time (LT), stoppage time (ST), and their ratio, transfer (TR) phases, and half court and full court actions. The frequency of occurrence of changes of activities was n = 576 ± 110, one every 2.56 seconds of LT. Total HIA was 8.5 ± 1.8% of LT and no significant differences between quarter periods were observed. In general, players performed linear sprints (48.3 ± 2.9%) over 1-5 m distance (56.8 ± 5.6%). The occurrence of RSE was 4.4 ± 1.7, with 58.6 ± 18.5% passive recovery between sprints. Team analysis showed no significant difference between games for LT and ST phases (ratio = 1.18 ± 0.25). For game analysis, LT and ST were 43.4 ± 7.8% and 51.1 ± 8.4%, respectively. A difference between games was found for half court actions (p < 0.01) and TR phases (p </= 0.05). Moreover, 1 TR and 2 TR were the most performed (45.3 and 23.9%) actions. These results encourage coaches to include repeated sprint ability with mainly linear and short sprints into a comprehensive training program.